Evaluation of Childhood Firearm Deaths Autopsies in Diyarbakır: Evaluation of Childhood Firearm Deaths Autopsies in Diyarbakır - Çom, Uğur; Gümüş, Burak (The Bulletin of Legal Medicine, 2022)
Objective: The medical findings, characteristics and investigation information of childhood firearm deaths autopsied in Diyarbakır are examined. İt is aimed to discuss the effects of possession of firearms on children and possible solutions to prevent similar incidents.Methods: Deaths due to firearm injuries in individuals under the age of 18 who were autopsied between 2014 and 2018 by the Council of Forensic Medicine, Diyarbakır Forensic Medicine Group Presidency are analyzed retrospectively through autopsy reports.Results: 5.7% of autopsy of firearm deaths occurred in childhood. In our study, 62 cases (92.5%) are between the ages of school period. The number of male cases are 43 (64.2%), while the number of female cases are 24 (35.8%). While the suicide origin is observed more frequently in the cases (21 cases, 31.3%), origin of the murder and the accident is found less frequent (11 cases-16.4%, 8 cases 12%, respectively). In 54.1% (13 cases) of female cases, the etiology of suicide is evaluated. Short barreled weapons were used in 33 cases (49.2%), and long barreled weapons were used in 33 cases (49.2%). The number of cases with death at the scene is 42 (62.6%), and 25 (37.4%) cases died in the hospital. There is a single gunshot wound in 59 cases (88%), and more than one gunshot wound is detected in 8 cases (12%).Conclusion: Preventing children's access to firearms, controlling individual armament, and increasing social awareness can reduce firearm deaths.
Keywords: Child; Firearm; Autopsy; Death